2019
DOI: 10.1021/acsanm.9b01755
|View full text |Cite
|
Sign up to set email alerts
|

Fe/Fe3O4@N-Doped Carbon Hexagonal Plates Decorated with Ag Nanoparticles for Microwave Absorption

Abstract: Electromagnetic (EM) interference and radiation affecting human health and the operation of precision electronic devices have drawn considerable attention in recent years. Herein, a promising microwave-absorbing material, Ag nanoparticles (AgNPs)-decorated Fe/Fe 3 O 4 @N-doped carbon (NC) composite, was designed and fabricated with the Fe 2 O 3 @polydopamine@Ag hexagonal plates as the precursor. Crystalline structure, phase conversion, micromorphology, static magnetic properties, and EM characteristics of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…The C 1s spectra can be divided into four peaks of 284.8 eV (C–C), 286.0 eV (C–O), 286.0 eV (CO), and 293.72 eV (O–CO) as shown in Figure a . In the Fe 2p spectra (Figure b), the Fe 0 2p 3/2 and Fe 0 2p 1/2 peaks appear at 706.8 and 720.4 eV, respectively, originating from Fe 3 C. The existence of nonzero valence iron including Fe 2+ 2p 3/2 (710.8 eV), Fe 2+ 2p 1/2 (724.1 eV), Fe 3+ 2p 3/2 (712.8 eV), and Fe 3+ 2p 1/2 (725.8 eV) indicates the formation of a passivating layer, and the satellite peaks (716 and 719 eV) originate from the high spin–orbit of Fe 2+ and Fe 3+ . , In addition, the increasing temperature led to the enhancement of the Fe 2p signal intensity, which indicates that more Fe elements are present on the surface of the composite material. This can attributed to the high temperature, which gives rise to significant consumption of the organic carbon resource during the carbothermal process resulting in the feature of nanosized magnetic metallic alloys wrapped by a thinner carbon layer, and the Fe-based alloys were easily oxidized.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The C 1s spectra can be divided into four peaks of 284.8 eV (C–C), 286.0 eV (C–O), 286.0 eV (CO), and 293.72 eV (O–CO) as shown in Figure a . In the Fe 2p spectra (Figure b), the Fe 0 2p 3/2 and Fe 0 2p 1/2 peaks appear at 706.8 and 720.4 eV, respectively, originating from Fe 3 C. The existence of nonzero valence iron including Fe 2+ 2p 3/2 (710.8 eV), Fe 2+ 2p 1/2 (724.1 eV), Fe 3+ 2p 3/2 (712.8 eV), and Fe 3+ 2p 1/2 (725.8 eV) indicates the formation of a passivating layer, and the satellite peaks (716 and 719 eV) originate from the high spin–orbit of Fe 2+ and Fe 3+ . , In addition, the increasing temperature led to the enhancement of the Fe 2p signal intensity, which indicates that more Fe elements are present on the surface of the composite material. This can attributed to the high temperature, which gives rise to significant consumption of the organic carbon resource during the carbothermal process resulting in the feature of nanosized magnetic metallic alloys wrapped by a thinner carbon layer, and the Fe-based alloys were easily oxidized.…”
Section: Resultsmentioning
confidence: 97%
“…The XPS survey recorded the spectra signals of C, N, O, Fe, and Zn (Figure S6), which is consistent with the elemental mapping (as orbit of Fe 2+ and Fe 3+ . 37,38 In addition, the increasing temperature led to the enhancement of the Fe 2p signal intensity, which indicates that more Fe elements are present on the surface of the composite material. This can attributed to the high temperature, which gives rise to significant consumption of the organic carbon resource during the carbothermal process resulting in the feature of nanosized magnetic metallic alloys wrapped by a thinner carbon layer, and the Fe-based alloys were easily oxidized.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, it can be reasonably that the deeper carbothermal reaction of Ni 2+ and Fe 2+ ions induced by the rising calcining temperature would introduce more significant disorder of generated graphite carbon in NFCR samples. 19 For investigation of the details of surface element valence and chemical bonding states in NFCR samples, X-ray photoelectron spectroscopy detection and analysis of the NFCR-600 sample have been carried out as an example. As shown in Figure 4a, it can be found that a distinct profile feature of several merged broad peaks has been recorded in the Fe 2p orbit of the NFCR-600 sample, which can be further deconvolved into eight separated peaks.…”
Section: Resultsmentioning
confidence: 99%
“…At present, the absorbents used to study the absorption properties of magnetic coatings include: metallic iron powder, ferrite, hydroxy iron, iron wire ber and other magnetic materials. The absorption of electromagnetic wave mainly depends on the magnetic polarization effects such as hysteresis loss, eddy current loss, domain wall resonance, aftereffect loss and residual loss [12][13][14][15]. The absorbents used in dielectric absorbing coating include graphite powder, carbon nanotube, carbon ber, calcium titanate, magnesium titanate, barium titanate, spinel, zinc oxide and other dielectric materials.…”
Section: Introductionmentioning
confidence: 99%